Analysis of provably secure on-demand source routing in MANET - MAO Li-qiang1; MA Jian-feng1; LI Xing-hua1 (Tongxin xuebao)
A formal model tailored to the security analysis of on-demand source routing protocols in MANET was analyzed, and the improper manipulations such as mergence of the adjacent adversarial nodes in the model and the flaw in the proof for endairA were indicated. A new hidden channel attack to endairA was presented, which shows that endairA is not provably secure even in their model.